1995
DOI: 10.1016/s0022-5223(95)70105-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tracheal allograft revascularization and transplantation

Abstract: The feasibility of tracheal allotransplantation with a fascial vascular carrier was examined in three groups with varied dose sequences of immunosuppression. A control group (group 1) received no medication. The three experimental groups were given daily cyclosporine intramuscular doses of 5 mg/kg (group 2), 5 mg/kg plus 3 mg/kg methylprednisolone (Solu-Medrol) (group 3), and 10 mg/kg (group 4) for 6 weeks or until death. Grafts were assessed by silicone dye infusion of the artery of the fascial flap to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 10 publications
2
49
0
4
Order By: Relevance
“…Triple immunosuppression therapy was started intravenously and maintained orally. (1). The membranous trachea was removed and the cartilaginous trachea was placed over the dissected recipient fascia and wrapped with this fascia (arrows-2).…”
Section: Case Reportsmentioning
confidence: 99%
“…Triple immunosuppression therapy was started intravenously and maintained orally. (1). The membranous trachea was removed and the cartilaginous trachea was placed over the dissected recipient fascia and wrapped with this fascia (arrows-2).…”
Section: Case Reportsmentioning
confidence: 99%
“…In 1994, a 2-stage tracheal transplant was described in rabbits using a fascial flap. 5,15 The tracheal graft was implanted heterotopically into the lateral thoracic fascia for revascularization, and the graft was orthotopically transplanted into the trachea; the results were successful, and the optimal time for the second stage was 2 to 3 weeks after the first stage. 5,15 However, this technique was not applied to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have suggested that tracheal allograft is a curative option for treating long-segment tracheal defects. [4][5][6] However, the tracheal allograft lacks an identifiable vascular pedicle that would allow direct vascular anastomosis to the blood vessels in the recipient's neck. Therefore, the safe restoration of the blood supply of the graft is a key factor to achieve successful outcomes of tracheal anastomoses.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect revascularization of a donor trachea is perfectly feasible, as demonstrated by the successful outcome of tracheal allografts and of autografts using vascularized fascia flaps in laboratory animals and humans (Buckwalter, 1998, Delaere et al, 1995. When this recipient tissue is perfused by an identifiable vascular pedicle, a microvascular transfer can be performed after the prefabrication step ).…”
Section: Reconstruction Of Long-segment Stenosis Of the Tracheamentioning
confidence: 99%